Systematization of Intellectual Property Objects for Forensic Purposes - G. G. Omel’yanyuk; V. V. Gulevskaya; A. S. Savenko (Теория и практика судебной экспертизы)
Correlation of the concepts of the object of forensic intellectual property investigation and the object of intellectual property is contemplated. The attributes of these objects are analyzed, in particular the intangible nature of intellectual property objects and the tangible character of the objects of forensic intellectual property investigation. A distinction is made between the concepts of ‘intellectual property’, ‘industrial property’ and ‘intangible assets’. The proposed systematization of intellectual property objects for forensic purposes is based on current practices in court ordered forensic intellectual property investigations. The case is made for setting up a new species of forensic investigation in the system of the Russian Ministry of Justice, as well as four new forensic science specialties: (1) investigation of items covered by copyright and related rights, (2) investigation of objects of patent rights and unconventional objects, (3) investigation of brand identities, (4) valuation of intellectual property objects.